2018
DOI: 10.1007/s11356-018-2912-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil phosphatase activities to contamination with two types of tar oil

Abstract: Tar oil is a complex mixture of hydrocarbon compounds obtained from high-temperature distillation of coal tar. It has been used for over 100 years from now to protect wood and has been applied to wood products, primary utility poles, and railroad ties by pressure methods. Composition of the tar oil depends on the source and typically consists of 85% polycyclic aromatic hydrocarbons (PAHs), 10% phenolic compounds, and 5% heterocyclic compounds. In this research, we performed the laboratory experiment to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…In particular, almost a 6-fold enhancement of the activity of dehydrogenases in the soil exposed to the pressure of diesel oil and its 0.6-fold suppression in the soil polluted with unleaded petroleum compared to the control soil may be due to the fact that dehydrogenases are intracellular enzymes which are strongly associated with the number and biomass of microorganisms [68]. Opposite effects of both tested substances on the enzymatic activity are attributable to significant differences in their physical and chemical properties [72].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, almost a 6-fold enhancement of the activity of dehydrogenases in the soil exposed to the pressure of diesel oil and its 0.6-fold suppression in the soil polluted with unleaded petroleum compared to the control soil may be due to the fact that dehydrogenases are intracellular enzymes which are strongly associated with the number and biomass of microorganisms [68]. Opposite effects of both tested substances on the enzymatic activity are attributable to significant differences in their physical and chemical properties [72].…”
Section: Discussionmentioning
confidence: 99%
“…Fyre-Zyme is a rich source of simple sugars, amino acids, and various biogenic factors. Therefore, changes in the content of elements in the soil may occur after the introduction of this enzyme preparation [9]. Moreover, the study carried out by Krzysko-Łupicka et al [36] revealed that the introduction of an aqueous solution of Fyre-Zyme enzyme preparation at a concentration of 6%, at a dose of 10% (w/w), to the soil contaminated with oil-derived substances increased the effectiveness of the hydrocarbon removal.…”
Section: Corgmentioning
confidence: 99%
“…Contamination of the soil with light crude oil fractions mainly stimulated the activity of oxidoreductases [3], but inhibited the activity of hydrolases [37], which was also confirmed by the results of the present study. On the other hand, the introduction of heavier crude oil fractions such as diesel oil, spent engine oil, or coal tar creosote into the soil negatively impacted the activity of all soil enzymes [9,17,31,38,39]. An analysis of the effect of Fyre-Zyme preparation (IF FZ ) on DHA in the uncontaminated and petrol contaminated soil, based on the values of the enzyme coefficients, indicated that the values were close to 1, on all measurement dates, for each type of preparation application.…”
Section: Corgmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Western European Institute for Wood Preservation (WEI-IEO), this amount of BaP is also a characteristic of type C coal tar creosote, which is obtained from the coal tar fraction with medium boiling point and low odor intensity. GX-Plus type is a mixture of coal tar creosote type C and mineral oils [ 6 ].…”
Section: Introductionmentioning
confidence: 99%